The Effect of Using Two Training Methods to Develop the Muscular Ability of The Arms of The Participants in The Bodybuilding Halls - Halgurd Sherzad Mohammed; Ahmed Abdulqader Hussen Rasul (QALAAI ZANIST JOURNAL, 2023)
- Detection of the effect of training methods on the development of muscle strength of the arms in bodybuilders (youth). The researchers used the training curriculum for its suitability and the nature of the study and research, and the researchers used the design of the two experimental groups with pre- and post-testing, and the researchers selected the research sample in a deliberate way. This is what the researchers did, if they were divided into two experimental groups, the first group works on the weighting method, while the second group works on the mitigation approach (10) ten players, and they were bodybuilders of the youth category (20) years old and in the Sardar Hall for bodybuilding. SPSS The researchers used the statistical bag from the mean and standard deviation for independent sample T & Law. Conclusions - The proposed training methods contributed significantly to the development and improvement of the muscular ability of the arms and both groups I and II have two experiments. The two proposed training aids have been instrumental in developing players’ levels towards better performance of muscle exercise. - Training methods have a positive impact on increasing muscle capacity in bodybuilding players (youth group). Recommendations - The researchers recommend the introduction of the proposed training methods in the training curricula to different age groups for the most part on the problems faced by the player at the beginning of his training life in the sport of bodybuilding, which need a high muscular ability in the muscle to overcome body weight. -The researchers recommend using the heavy-duty method for lightweight players and using the mitigation method for players with heavy weights. - Using new training methods and conducting more studies in this field and for other age groups as well as for other events and sports such as weightlifting.